THE CONTRIBUTION OF HAJI ANIF TO THE DEVELOPMENT OF COMMUNITY-BASED ISLAMIC RELIGIOUS EDUCATION IN NORTH SUMATRA: A BIOGRAPHICAL STUDY (Pena Cendekia Insani, 2026)
This study aims to analyze Haji Anif’s contribution to the development of Islamic Religious Education in North Sumatra and to identify the Islamic educational values he inherited. Using a qualitative approach with a biographical study design, data were collected through interviews, documentation, and literature review. The findings show that Islamic Religious Education was developed through educational institutions, mosques, foundations, da’wah activities, and social programs based on Islamic philanthropy. The study also identified social responsibility, charity (sadaqah), love for the Qur’an, independence, and sustainability as key educational values promoted by Haji Anif. The study concludes that Haji Anif played a significant role in establishing a sustainable community-based Islamic Religious Education ecosystem that integrates education, da’wah, philanthropy, and social empowerment.